Analysis of Complaint Behavior To E-Customer Satisfaction Customer Loyalty Tiktok Shop - kurniawan, Cristoporus Esandra Murta; Rusfian Effendi; Irfan Handoko; Muhammad Deny (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study aims to analyze the effect of complaint behavior on customer satisfaction and customer loyalty, as well as the mediating role of customer satisfaction among TikTok Shop users. The research employs a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through the SmartPLS version 4 application. Based on the test results, it was found that complaint behavior has a positive and significant effect on customer satisfaction. Furthermore, complaint behavior also has a positive and significant effect on customer loyalty. In addition, customer satisfaction has been proven to have a positive and significant effect on customer loyalty. The mediation analysis results show that customer satisfaction significantly mediates the effect of complaint behavior on customer loyalty indicating an indirect-only mediation effect. These findings emphasize that enhancing customer satisfaction on TikTok Shop can strengthen the relationship between complaint behavior and customer loyalty. Therefore, TikTok Shop needs to improve the quality of its complaint-handling processes to enhance satisfaction and maintain user loyalty sustainably. Keywords: Complaint Behavior, Customer Satisfaction, Customer Loyalty, TikTok Shop Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh complain behavior terhadap customer satisfaction dan customer loyalty, serta peran mediasi customer satisfaction pada pengguna TikTok Shop. Penelitian ini menggunakan pendekatan kuantitatif dengan metode Partial Least Square–Structural Equation Modeling (PLS-SEM) Berdasarkan hasil pengujian, diperoleh bahwa complain behavior berpengaruh positif dan signifikan terhadap customer satisfaction Selanjutnya, customer satisfaction terbukti berpengaruh positif dan signifikan. Hasil analisis mediasi menunjukkan bahwa customer satisfaction mampu memediasi pengaruh complain behavior terhadap customer loyalty secara signifikan yang menunjukkan adanya efek indirect-only mediation. Temuan ini menegaskan bahwa peningkatan kepuasan pelanggan TikTok Shop dapat memperkuat hubungan antara perilaku komplain dan loyalitas pelanggan. Oleh karena itu, TikTok Shop perlu meningkatkan kualitas penanganan keluhan pelanggan untuk memperkuat kepuasan serta mempertahankan loyalitas pengguna secara berkelanjutan. Kata kunci: Complain Behavior, Customer Satisfaction, Customer Loyalty, TikTok Shop,